Progresso espaço-temporal da fusariose em plantios de pimenta-do-reino - Rocha Neto, Francisco de Castro (2013)
Black pepper is the third item on Espirito Santo's agrocultural exportation agenda. Fusariosis is one of the culture1s main dieseases, it causes the death of the plant and makes the economic production unworkable. The space-time study is an important tool on the diagnosis and orientation on the handling of plant diseases. The main goal of this work is to know fusariosis' space-time behavior in black pepper's culture. The experiment has been conducted in field conditions, in the north of Espirito Santo, between July 2010 and January 2012. Twenty plots were chosen, in different black pepper tillages, with 500 plants each, divided in four groups, according with tillage age, 1, 2, 3, 4 and 5 years. Fusariosis incidence has been evaluated every two months. On the field of time it has been made a study using the curve of disease progress, the monomolecular model proved to be the best on the epidec's description. The space behavior demonstrated an initial distribution of the disease at random, followed by a change of model to aggregate, pointing to a slow process of plant to plant disease dissemination, characteristic to pathogens found in the soil.